Interaction of Pinostrobin Oxime and Leukomizin with reactive oxygen species in model systems - Ye. A. Rodnova; V. V. Ivanov; V. S. Chuchalin; A. N. Melentiyeva; L. I. Arystan; Z. T. Shulgau; S. M. Adekenov (Бюллетень сибирской медицины)
Free radical processes are a common universal mechanism of cellular damage in the pulmonary and cardiovascular diseases, diseases of the pancreas and liver, atherosclerosis, cataracts, etc. In this work, we investigated the interaction of the pinostrobin oxime and leucomisine with active forms of oxygen. The study of the interaction of the pinostrobin oxime and leucomisine with a stable radical 2,2-diphenyl-1-picrylhydrazyl, superoxide anion radical, hydroxyl radical, and the effects on stimulated prooxidants (hydrogen peroxide) lipid peroxidation in post-nuclear fraction of liver. As comparison drugs used substances with known antioxidant and antiradical activity - butylated hydroxytoluene, quercetin, and mannitol. The experiments showed that pinostrobin oxime and leucomisine exhibit moderate antiradical activity against the studied free radicals.